2009
DOI: 10.1128/ec.00123-09
|View full text |Cite
|
Sign up to set email alerts
|

A Contiguous Compartment Functions as Endoplasmic Reticulum and Endosome/Lysosome in Giardia lamblia

Abstract: The dynamic evolution of organelle compartmentalization in eukaryotes and how strictly compartmentalization is maintained are matters of ongoing debate. While the endoplasmic reticulum (ER) is classically envisioned as the site of protein cotranslational translocation, it has recently been proposed to have pluripotent functions. Using transfected reporter constructs, organelle-specific markers, and functional enzyme assays, we now show that in an early-diverging protozoan, Giardia lamblia, endocytosis and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
99
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(111 citation statements)
references
References 43 publications
12
99
0
Order By: Relevance
“…Possibly supporting this hypothesis, giardial clathrin and AP-1 were observed not only on ER-exist sites but also in PVs (Marti et al, 2003a;Marti et al, 2003b;Touz et al, 2004;Gaechter et al, 2008). As we said, the ER tubular-vesicular network apparently extends to and contacts the PVs in the periphery of the cell (Abodeely et al, 2009b) but it was recently reported that no ER membranes invade the space occupied by PVs (Faso and Hehl, 2011). An explanation that reconciles these observations might be that at least some of the clathrin-dependent trafficking in Giardia involves tubular carriers that extend from the ER-exit sites to the peripheral cytoplasm until they meet with distally located PVs.…”
Section: Clathrinsupporting
confidence: 69%
See 4 more Smart Citations
“…Possibly supporting this hypothesis, giardial clathrin and AP-1 were observed not only on ER-exist sites but also in PVs (Marti et al, 2003a;Marti et al, 2003b;Touz et al, 2004;Gaechter et al, 2008). As we said, the ER tubular-vesicular network apparently extends to and contacts the PVs in the periphery of the cell (Abodeely et al, 2009b) but it was recently reported that no ER membranes invade the space occupied by PVs (Faso and Hehl, 2011). An explanation that reconciles these observations might be that at least some of the clathrin-dependent trafficking in Giardia involves tubular carriers that extend from the ER-exit sites to the peripheral cytoplasm until they meet with distally located PVs.…”
Section: Clathrinsupporting
confidence: 69%
“…Recently, it was shown that a mechanism of receptor-mediated endocytosis occurs in this organism, with specific molecules selectively directed to the PVs through a classical endocytic mechanism (Rivero et al, 2010;. These data suggest that uptake of soluble material into PVs is not selective at this step but is still capable of redirecting specific molecules to the TVN (Hernandez et al, 2007;Abodeely et al, 2009b). In terms of receptor-mediated endocytosis, movement between vesicles could be observed (Figure 4), which suggests, not only that Giardia possesses a refined and conserved mechanism of endocytosis, but also that the PVs population might not be as homogeneous as was thought but rather organized depending on their functions (Rivero & Touz, unpublished).…”
Section: The Endosomal/lysosomal System Of Giardiamentioning
confidence: 99%
See 3 more Smart Citations